Efektivitas ekstrakurikuler keputrian dalam meningkatkan pemahaman fikih wanita pada siswi SMA Negeri 9 Medan - Napitupulu, Tiara Angraini; Imran , Ali; Darlis, Ahmad (Kaisa: Jurnal Pendidikan dan Pembelajaran, 2024)
The research entitled "Effectiveness of Girls' Extracurriculars Improving the Understanding of Women's Jurisprudence among Female Students of SMA Negeri 9 Medan", which the background is that adolescence is the beginning of a Muslim obliged to comply with Islamic law. Female students must understand obligations and responsibilities answer as a Muslim woman. So educational institutions have programs helping female students in this matter, namely extracurricular girlhood. This research uses a qualitative research method, case study type. The data collection techniques are interviews, observation and documentation. Data analysis techniques are data reduction, data presentation and drawing conclusions. The results of the research are (1) Extracurricular planning for inner women's affairs Increasing women's understanding of jurisprudence includes: a) setting goals, namely to increase female students' understanding of women's jurisprudence. b) plan material, namely menstruation, istihadah, postpartum, women's private parts, Muslim women's clothing. c) determine strategies and methods, namely expository strategy, lecture method and question and answer. d) development of learning resources. (2) Princesses are performed on Fridays at 11.30. (3) The evaluation used is evaluation of description tests, assignments and oral test. Keywords: effectiveness, extracurricular girlhood, women's jurisprudence